2019
DOI: 10.1111/jop.12930
|View full text |Cite
|
Sign up to set email alerts
|

Casticin inhibits invasion and proliferation via downregulation of β‐catenin and reversion of EMT in oral squamous cell carcinoma

Abstract: Background Casticin expresses multiple anti‐cancer activities, whereas the effect of casticin on oral squamous cell carcinoma (OSCC) is still unclear. β‐catenin signaling plays a crucial role in the epithelial‐mesenchymal transition which is closely related to tumorigenesis. Herein, we aimed to study the functions of casticin on invasion and migration of OSCC, and clarify whether the effect of casticin on OSCC has a relationship with β‐catenin signaling. Methods Human OSCC cell lines UM1 and HSC‐3 were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…2D ). Since EMT is a key process in potentiating tumour migration and invasion ( 7 ), the role of hypoxia in the invasion and migration of OSCC cells was assessed by Transwell assays. Hypoxia was found to significantly enhance HN6 and HSC3 cell migration and invasion compared with normoxic cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2D ). Since EMT is a key process in potentiating tumour migration and invasion ( 7 ), the role of hypoxia in the invasion and migration of OSCC cells was assessed by Transwell assays. Hypoxia was found to significantly enhance HN6 and HSC3 cell migration and invasion compared with normoxic cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At present, surgery combined with radiotherapy and chemotherapy is the primary treatment option for oral cancer. However, the 5-year survival rate of patients with oral cancer has not significantly improved over the past decade ( 6 , 7 ). The invasive and metastatic ability of tumour cells is one of the main factors affecting the prognosis of patients ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of β-catenin induces proliferation, invasion and migratory activities in tumor cells, while its downmodulation can negatively regulate these tumorigenic processes. Additionally, casticin reversed epithelial-mesenchymal transition (EMT) in a dose-dependent manner [99]. In a second study, casticin inhibited cell viability by upregulating ROS and Ca2+ ions, decreasing ∆Ψm; activating caspase-3, -8 and -9 and upregulating AIF and cytochrome c. Casticin also has the ability to inhibit EMT transitioning, where epithelial cells become more migratory by losing their polarity and junctions.…”
Section: Casticin and Oral Cancermentioning
confidence: 97%
“…It is characterized by increasing the expression of mesenchymal genes such as fibronectin, vimentin and N-cadherin and suppressing the expression of epithelial genes such as ocludin and E-cadherin [108][109][110][111][112][113][114][115]. It has been found that various concentrations of casticin can reverse the EMT process by increasing E-cadherin expression while inhibiting N-cadherin in oral squamous cell carcinoma (OSCC) UM1 cells [99], ovarian cancer SKOV3 cells [103] and liver cancer stem cells (LCSCs) derived from the SMMC-7721 cells [79]. After exposure to casticin, mRNA levels of Twist1 and N-cadherin decreased with the time progressed, most notably at 24 h in SKOV3 cells [103].…”
Section: Effect Of Casticin On Epithelial-mesenchymal Transition (Emt)mentioning
confidence: 99%
See 1 more Smart Citation